2020
DOI: 10.1063/1.5122782
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical theories as initial value problems

Abstract: Motivated by the initial value problem in semiclassical gravity, we study the initial value problem of a system consisting of a quantum scalar field weakly interacting with a classical one. The quantum field obeys a Klein-Gordon equation with a potential proportional to the classical field. The classical field obeys an inhomogeneous Klein-Gordon equation sourced by the renormalised expectation value of the squared quantum field in a Hadamard state, Ψ|Φ 2 Ψ . Thus, the system of equations for the scalar fields … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…where we have used the relation |χ 0 k | = 0. Recalling the estimates (29), having shown the integrability of f 3 at any time in (37) and knowing how to control χ k and its functional derivatives, the statements of the Proposition follow.…”
Section: Expectation Values Of φ 2 and Its Time Derivativementioning
confidence: 90%
See 1 more Smart Citation
“…where we have used the relation |χ 0 k | = 0. Recalling the estimates (29), having shown the integrability of f 3 at any time in (37) and knowing how to control χ k and its functional derivatives, the statements of the Proposition follow.…”
Section: Expectation Values Of φ 2 and Its Time Derivativementioning
confidence: 90%
“…The price to pay is that the dimension of that dynamical system is infinite and furthermore, for the case of a generic state, it is not clear if all these moments correspond to those obtained for a meaningful quantum state. Another recent study of the initial value problem associated with semiclassical equations can be found in [37]. Furthermore, numerical analyses have been performed in the past by Anderson in the study of effects of particle creation in the early universe [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Before addressing in full detail the main equations of our model, we present the framework that underlies our description of the space-time metric and that of the inflaton [6,[53][54][55][56][57]. The proposed model is based on the semiclassical gravity framework, in which gravity is treated classically and the matter fields are treated quantum mechanically.…”
Section: The Collapse Proposal and The Primordial Power Spectrummentioning
confidence: 99%
“…The interested reader can consult Refs. [54][55][56][57]; in those works the formalism of the collapse proposal within the semiclassical gravity framework has been developed. In the present paper, we will only make use of the most relevant equations.…”
Section: The Collapse Proposal and The Primordial Power Spectrummentioning
confidence: 99%
“…This has been significantly extended by Pinamonti and one of us [48] to full solutions of the SCE on FLRW spacetimes, including the energy constraint with initial values specified on a Cauchy surface, but still limited to the conformally coupled scalar field, and a particular choice of renormalization parameters and quantum state. Other recent work related to the SCE includes: [26], where numerical solutions to the equations presented here are analyzed; [40], where yet another approach to solving the SCE is developed; [36], where a simplified semiclassical problem is studied as an initial value problem; [51] and [35], where solutions in static spacetimes are analyzed.…”
Section: Introductionmentioning
confidence: 99%